Polysomnographic features of pregnancy: A systematic review. (April 2020) - Garbazza, Corrado; Hackethal, Sandra; Riccardi, Silvia; Cajochen, Christian; Cicolin, Alessandro; D'Agostino, Armando; Cirignotta, Fabio; Manconi, Mauro
Summary: Symptoms of sleep disturbances are common among pregnant women and generally worsen across gestation. Pregnancy-related sleep disorders are not only associated with a poor quality of life of the affected mothers, but also with adverse perinatal outcomes, including perinatal depression, gestational diabetes, preeclampsia, and preterm birth. The current knowledge about the impact of sleep disorders during pregnancy largely derives from the results of sleep surveys conducted in various populations. However, the number of studies examining changes in objective sleep variables during pregnancy via polysomnography has progressively increased in recent years. Here we systematically reviewed the polysomnographic studies available in the literature with the aim to describe the sleep pattern and to identify possible markers of sleep disruption in pregnant women. Based on our analysis, subjective worsening of sleep quality across gestation is related to objective changes in sleep macrostructure, which become particularly evident in the third trimester. Pregnancy per se does not represent an independent risk factor for developing major polysomnography-assessed sleep disorders in otherwise healthy women. However, in women presenting predisposing factors, such as obesity or hypertension, physiological changes occurring during pregnancy may contribute to the onset of pathological conditions, especially sleep-disordered breathing, which must be carefully considered.